Digital currency and privacy - Kee-Youn Kang (Theoretical Economics, 2024)
We develop a monetary model in which a private company issues digital currency and uses payment data to estimate consumers' preferences. Sellers purchase preference information to produce goods that better match consumers' preferences. A monopoly arises in the digital currency industry, and digital currency is not issued if the inflation rate is sufficiently high. Due to reinforcing interactions between the value of preference information and trade volume, multiple equilibria (with and without digital currency) can exist depending on market structures for monetary exchanges. When left to market forces alone, socially efficient uses of payment data may not occur.
Keywords: E12; E40; E50; G10; 330; Digital currency; preference information; privacy; strategic complementarities; transaction data